Central line associated bloodstream infections in hospitalized children in Greece before and after implementation of a prevention bundle - Mougkou, Katerina; Gkentzi, Despoina; Kourlaba, Georgia; Kouni, Sofia; Kopsidas, Ioannis; Nteli, Charalampia; Zaoutis, Theoklis; Coffin, Susan (International Journal of Infection Control, 2015)
Data on central line (CL) - associated bloodstream infections (CLABSIs) in neonates and children in Greece are limited. In this study we aimed to assess the epidemiology and microbiology of CLABSIs in children’s hospitals in Greece using an active surveillance system and to assess the impact of a central line bundle on the incidence of CLABSIs.The study was conducted by active surveillance for CLABSIs over an 18-month period (September 2012 – February 2014) in the two largest children’s hospitals in Greece. After six months of surveillance, a CLABSI prevention bundle was introduced.There were 4.07 infections per 1,000 CL days across all participating units in the baseline period. The infection rate during the intervention period decreased by 35% to 2.58 per 1,000 CL days (95% CI: 0.64 (0.55 – 0.75)). Stratified analysis by ward type revealed the highest baseline CLABSI rate for patients in paediatric intensive care units (16.67 per 1,000 CL days), where the greatest reduction (50%) in the CLABSI rate was detected after the intervention. Overall, 48 (60%) of the isolated pathogens were Gram negative, where 4 (8.3%) were found to be resistant to carbapenems and 22 (45.8%) to one or more of third generation cephalosporins.Implementation of the prevention bundle produced a significant reduction of the CLABSIs in the Greek paediatric hospitals. The high CLABSI rates and the levels of antimicrobial resistance of pathogens identified highlight the importance of establishing antimicrobial stewardship and active surveillance programs in Greece, a country with high rates of healthcare-associated infections during a period of financial crisis.